Ageing as a Unique Experience: Interdisciplinary Approaches to Ageing and Later Life from Social and Humanities Perspectives - Stončikaitė, Ieva; Vidovićová, Lucie (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Ageing is a diverse and multifaceted experience that is unique to each person. The process of ageing is lived differently according to each individual's socio-cultural, historical, religious, and political context, among other factors. However, the stereotype of homogeneity is still one of the strongest aspects related to later life. This Special Issue covers manuscripts of original research that critically explore the experience of old age and the process of growing older from the social sciences and humanities perspectives. It also explores the topics pertaining to social gerontology, cultural and literary gerontology, environmental gerontology, gerotechnological studies, social anthropology, gender studies, body politics, sexuality, active and healthy ageing, space and place, age-friendly politics and other themes. The published articles collect arguments that show the variables and uniqueness of later life, and expand on the current theoretical frameworks in the field of age studies and beyond. The overall aim of this Special Issue was to broaden the gerontological scholarship and develop critical thought of old age and the life course beyond the merely biological processes of growing older and their sociocultural constructs. This Special Issue can be of interest to scholars, practitioners, stakeholders, care workers and individuals who are concerned with the dynamics of ageing as well as current and future dialogues on the unique experiences of ageing.